Meteorites a petrologic, chemical and isotopic synthesis - Hutchison, Robert (Cambridge University Press, 2006)
Meteorite research is fundamental to our understanding of the origin and early history of the Solar System. This text considers the mechanism and timing of core formation and basaltic volcanism on asteroids, and the effects of heating water-rich bodies.
Includes bibliographical references and index
Keywords: Meteorites; Meteorit; Gesteinskunde; Mineralogie